Immune dysregulation and lipid interactions in systemic lupus erythematosus-associated atherosclerosis: mechanisms and pathogenesis - Bilodeau, Philippe; Tselios, Konstantinos (Frontiers in Lupus, 2025)
Atherosclerosis is increasingly recognized as a chronic inflammatory process, involving intricate interactions among the endothelium, lipids, coagulation system, and components of both the innate and adaptive immune systems. In the context of systemic lupus erythematosus (SLE), these interactions are even further disrupted, contributing to accelerated atherosclerosis. This narrative review explores how immune system dysregulation plays a central role in the development of atherosclerosis in SLE patients, where cardiovascular disease remains the leading cause of mortality despite recent advancements. We aim to present a model based on current scientific evidence that compares the immune mechanisms driving atherosclerosis in the general population with the accelerated form observed in SLE patients, highlighting the key immunological distinctions that set SLE-associated atherosclerosis apart. Particular emphasis was given to the interactions between interferon, lipid alterations and adaptive immunity as mediators of atherogenesis. This model may help identify gaps in our understanding and generate new hypotheses for potential therapeutic targets to modulate immune responses within atherosclerotic plaques.